KERJASAMA PT PELINDO I INDONESIA DENGAN PORT OF ROTTERDAM BELANDA DALAM PENGEMBANGAN PELABUHAN KUALA TANJUNG - Kinanti, Ajeng Setry; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Indonesia is an archipelagic state composed of 1/3 of the land region and 2/3 oceans region. Indonesia has realized that it is an opportunity for Indonesia to improve its state’s economy through the realization of Indonesia as a maritime axis of the wolrd. On October 13, 2014, Indonesia represented by PT Pelindo I and Netherland represented by Port of Rotterdam signed a cooperation agreement in developing port Kuala Tanjung to become an International Hub Port. On August 25, 2015, Indonesia signed a follow-up cooperation. And on November 23, 2016, Indonesia signed a cooperation agreement and formed a joint venture in developing Port Kuala Tanjung to become International Hub Port. This research uses a neo-liberalism perspective which is the supported by the international cooperation theory and foreign direct investment concept. This study also used a nation-state analysis level with a research focus on the factors that caused Indonesia in collaboration with Netherland in developing Kuala Tanjung Port, and all of data, arguments, fact in this research afterwards using a qualitative explanation method. This research then formulates answer of the research question related to the factors which influence cooperation Indonesia-Netherland in developing port of Kuala Tanjung. There are five important points that led to the cooperation, first, Global shipping condition, second, Indonesia’s vision to be world maritime axis, third, Inadequate maritime infrastructures of Indonesia, forth, the potency of Kuala Tanjung Port to become International Hub Port, and Indonesia’s interest for information and technology transfer, foreign direct investment and strategic partnership. Keywords: Cooperation, Foreign Direct Invesment (FDI), Hub Port International, Joint Venture, Visi Poros Maritim Dunia.